Mechanism of heme oxygenase-1 regulation of ferroptosis in vascular dementia - Xin-yi Zou; Luo-yang Cai; Jin Zhang; Ying Yuan; Jie Song; Jie Song; Zhao-duan Hu; Zhao-duan Hu; Zhao-duan Hu; Xiao-feng Ruan; Xiao-feng Ruan; Rui Peng; et al. (Frontiers in Molecular Neuroscience)
Vascular dementia (VaD) is a neurodegenerative disorder characterized by chronic oxygen insufficiency, leading to the generation of oxygen-free radicals, inflammatory responses, disturbances in iron metabolism, lipid peroxidation, and other pathological changes that disrupt intracellular homeostasis. These processes ultimately lead to neuronal death and cognitive dysfunction. Normal neurological functions depend on the capacity of the iron homeostatic system to regulate the balance of oxidative states. Imbalances in iron metabolism render nerve cells highly susceptible to cell death induced by iron accumulation. Ferroptosis is a process in which iron catalyzes the peroxidation of unsaturated fatty acid-rich lipids, with ferrous iron or lipoxygenase acting as catalysts and ultimately resulting in cellular demise. Heme oxygenase-1 (HO-1) is a critical enzyme involved in the cellular response to oxidative stress and is essential for regulating signaling pathways linked to iron-mediated cell death. It protects neuronal cells by mitigating oxidative stress, reducing inflammation, and enhancing mitochondrial function, thereby alleviating cerebrovascular injury and slowing the progression of VaD. This paper provides a theoretical framework for understanding and potentially treating VaD-related neuronal injury through the investigation of ferroptosis mechanisms, the biological functions of HO-1, and its role in regulating ferroptosis.